Molecular diffusion coefficients of organic compounds in water at different temperatures - J. M. P. Q. Delgado (2007)
Molecular (or tracer) diffusion coefficient data were obtained for 2-naphthol, benzoic acid, salicylic acid, camphor, and cinnamic acid in water at temperatures that differ significantly from ambient value. Experimental values were determined for the dissolution of 2-naphthol in water at 283 to 368 K, of benzoic acid in water at 283 to 338 K, of salicylic acid in water at 283 to 343 K, of camphor in water at 283 to 318 K, and of cinnamic acid in water at 283 to 318 K. Empirical correlations are presented for the prediction of molecular diffusion coefficient over the entire range of temperatures studied, and they are shown to predict the obtained data with very good accuracy.